LEGAL ANALYSIS OF LEGAL TREATMENT OF DETAINEES WHO HAVE VIOLATED PUBLIC ORDER (CASE STUDY: MEDAN IMMIGRANT PRISON) - Febri Hariono Nababan; Abdul Razak Nasution; T Riza Zarzani (PT. Sinergi Legal Publisher, 2024)
This research aims to find out: 1) the differences between Deteni and Rudenim and 2) how Implementation detainees are treated who violate public order. The type of approach used is qualitative research. This means research that describes, explains, analyzes and develops the legal construction of state sovereignty from an immigration perspective. The results of the research discussion are: 1) Detainees based on Law Number 6 of 2011 concerning Immigration Article 1 paragraph 35 are foreign residents of Immigration Detention Centers who have received a detention decision from Immigration officials. Foreigners in this case are people who are not Indonesian citizens. Meanwhile, the Immigration Detention Center is a Technical Implementation Unit that carries out immigration functions as a temporary shelter for foreigners who are subject to Immigration Administrative Action. 2) Legal treatment for detainees who violate public order will depend greatly on the type of violation committed, its severity, and the regulations in force at the immigration detention center.